A failure analysis of the exhaust valve from a heavy duty natural gas engine. (March 2018) - Khan, Muhammad Imran; Khan, Muhammad Arsalan; Shakoor, Abdul
Abstract: Increasingly stringent emission standards are changing the conditions that valve systems in heavy duty engines are exposed to. Increased pressures and temperatures are challenging system endurance. A consequence of these changing conditions is a reduction in the levels of soot production that had formerly generated protective films. In order to help combat this, nickel-based super alloys have been widely used in applications requiring strength at high temperature. This study presents a premature failure case of a set of exhaust valves belonging to a heavy duty natural gas engine; where the valves were manufactured from one of these alloys, the precipitation hardened Inconel-751. The failure occurred at approximately 5000 operating hours after its first commissioning, whilst the standard expected service life of the valves is 20, 000 h. Several examinations employing multiple techniques were carried out in order to identify the root cause of failure, whilst comparing results against those of a new valve. It was found that there was some mechanical lapse in proper sitting of the valve, which had been responsible for unwarranted overheating especially at thinner sections. Microstructure examination revealed that overheating had been responsible for a creep-rupture failure accentuated by precipitation of undesirable constituents at grain boundaries. Highlights: Failure of heavy duty natural gas engine exhaust valves occurred at low life. The valves, manufactured from Inconel-751, were analysed. Overheating was responsible for a creep-rupture failure. Overheating had also caused particle coarsening, leading to intergranular corrosion.